A study on risk factors and proportion of emergency peripartum hysterectomy in a tertiary care centre - Yadav, Bhaurao; Gandikota, Samanvitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Peripartum hysterectomy, though rare, is a high-risk procedure performed during or immediately after delivery. It is linked to increased morbidity, mortality, and significant healthcare costs, particularly affecting women wishing to preserve fertility. Major complications include transfusion requirements, re-exploration for persistent bleeding, febrile morbidity, severe surgical complications, and maternal death. Methods: This prospective study was conducted over 18 months (September 2022 to May 2024) at Vilasrao Deshmukh Government Medical College and Hospital, Latur. It included patients requiring emergency peripartum hysterectomy, both those presenting directly and those referred after undergoing the procedure elsewhere. Results: In this study, the majority of cases (12) occurred in individuals aged 35 and above, followed by 11 cases in the 26-34 age group and 7 cases in the 18-25 age group. Most patients had only primary education (43.32%), with 33.34% completing secondary education and 23.34% graduating from secondary education. A higher prevalence was observed in rural areas (56.66%) compared to urban locations (43.34%). Socioeconomically, most cases (73.34%) belonged to lower socioeconomic classes (III, IV, V), while 26.66% were from upper socioeconomic classes (I, II). Conclusions: Emergency peripartum hysterectomy is a critical, life-saving intervention, where timely execution and a multidisciplinary approach are essential for improving patient outcomes. Assessing its prevalence in society aids in identifying key risk factors, enabling early detection and a comprehensive strategy to safeguard maternal health.